The History of Accounting Reports In China - Brozovsky, John; Zhang, Zhilling (The International Journal of Accounting and Business Society, 1996)
Accounting and accounting reports in China are currently undergoing massive reform. This current change is a culmination of a number of historical effects. While accounting and accounting reports started early in China. They had a limited focus. Commerce was downplayed and reporting was primarily governmental. These reports were used at various times during the Chinese dynasties for performance evaluation and budgeting or simply to report governmental collections. While reporting changed and improved over time the general status of accounting reports stayed the same until the advent of western inï¬‚uences after the Opium War in I840. Since that time China has undergone several major societal and cultural upheavals. Each major societal change, of necessity changed the accounting and reporting system. However, the basic grass roots of reporting tended to resist change. ln I916 the Qing dynasty introduced new accounting rules but they and the following Nationalist government of China failed to actually implement them. The communistic government which followed easily adopted a central government reporting system that was much closer to the historical systems of the Chinese dynasties. lt has been only since I992 that a international (western) accounting system has been instituted in China.